Characteristics of farm based day care services for people with dementia – mapping the stakeholders’ views - Ingeborg Pedersen; Lina Ellingsen-Dalskau; Grete Patil (Wellbeing, Space and Society, 2022)
The study aimed to identify elements of importance for providing a good care environment in farm-based day care services for people with dementia. Nineteen stakeholders involved in farm-based dementia care participated in a two-phased mixed-method study (concept mapping). Quantitative analyses of 85 collected statements on what identified characteristics of such services formed a map consisting of 8 clusters representing the aggregated elements. Based on the map, a model was developed indicating interactions between the clusters. The farm context was the basis for creating a health promoting care environment facilitating tailored activities essential for person-centered care and wellbeing for the attendees.